Soybean GmSNF4 Confers Salt–Alkali Stress Tolerance in Transgenic Plants - Nan Ye; Jia-Shen Bian; Bai-Hui Zhou; Ling-Tao Yong; Ting Yang; Nan Wang; Yuan-Yuan Dong; Wei-Can Liu; Fa-Wei Wang; Hai-Yan Lv; Xiao-Wei Li (Plants)
In order to mitigate the reduction in soybean yield caused by soil salinization, a soybean gene, GmSNF4, which promotes plant tolerance to salt–alkali stress, was identified in this study. The STRING database was used to predict the interaction between GmSNF4 and GmPKS4. The GmPKS4 gene was experimentally shown to be involved in salt–alkali stress tolerance. Firstly, the yeast two-hybrid technique and bimolecular fluorescence complementation (BiFC) technique were used to confirm the interaction between GmSNF4 and GmPKS4: the AMPK-CBM-CBS1 conserved domain was thereby determined to be the region of the GmSNF4 protein involved in the interaction. Secondly, the GmSNF4 gene was induced by salt–alkali stress according to qRT-PCR analysis, and the GmSNF4 protein was localized in the nucleus and cytoplasm. Finally, analysis of GmSNF4’s role in resistance to salt–alkali stress in transgenic soybean plants showed that transgenic lines had better phenotypic, physiological, and stress-related gene expression than non-transgenic soybeans. Thus, GmSNF4 may play a significant role in plant salt–alkali stress tolerance.